A techno‐economic analysis framework for intensified modular systems. Issue 3 (5th March 2022) - Gazzaneo, Vitor; Watson, Madelynn; Ramsayer, Carlie B.; Kilwein, Zachary A.; Alves, Victor; Lima, Fernando V.
Abstract: In this work, a novel systematic techno‐economic analysis framework is proposed for costing intensified modular systems. Conventional costing techniques are extended to allow estimation of capital and operating costs of modular units. Economy of learning concepts are included to consider the effect of experience curves on purchase costs. Profitability measures are scaled with respect to production of a chemical of interest for comparison with plants of traditional scale. In the developed framework, a base case scenario is analyzed to identify the relevance of the economy of learning and cost parameters that are yet to be established for modular projects that will be deployed. Then, a sensitivity analysis step is conducted to define changes in relevant variables that benefit the construction of modular systems. In a final step, scenarios in which the modular technology presents break‐even and further reduction in cost are identified. A process model for a modular hydrogen unit is developed and used for demonstration of the proposed framework. In this application, process synthesis is carried out, including operability analysis for selection of feasible operating conditions. A comparison with a benchmark conventional steam methane reforming plant shows that the modular hydrogen unit can benefit from the economy of learning. A synthesized flowsheet for a modular steam methane reforming plant is used to map the decrease in natural gas price that must be needed for the plant to break even when compared to traditional technologies. Scenarios in which the natural gas price is low allow break‐even cost for both individual hydrogen units and the assembled modular plant. For such break‐even cases, the economy of learning must produce a reduction of 40% or less in capital cost when the natural gas price is under 0.02 US$/Sm 3 . This result suggests that the synthesized modular hydrogen process has potential to be economically feasible under these conditions. The developed tools can thus be used to accelerate the deployment and manufacturing of standardized modular energy systems.